915 PHENOTYPIC EXPRESSION AND OUTCOMES OF CARDIOMYOPATHY CAUSED BY TITIN TRUNCATING VARIANTS: TRANSLATIONAL INSIGHTS. (15th December 2022) - Perotto, Maria; Radesich, Cinzia; Paldino, Alessia; Ferro, Matteo Dal; Sinagra, Gianfranco
Abstract: Background: Titin truncating variants (TTNtv) represent the most prevalent genotype underlying dilated cardiomyopathy (DCM). Recent molecular studies provided initial evidence about different pathogenic mechanisms produced by different mutation sites of the truncating variant (A-Band vs non-A-band), possibly related to the presence or absence of truncated titin (TTN) peptides. However, to date, clinical studies on DCM patients carrying TTNtv failed to demonstrate any relevant clinical difference according to the titin band affected. We hypothesized this lack of variation could be partially explained by the selection bias of including only DCM phenotype patients. Thus, we studied the clinical phenotypes and outcomes of our entire population of subjects with pathogenic TTNtv regardless of phenotypic expression at the onset. Methods: We retrospectively analyzed a population of pathogenic TTNtv carriers, enrolled in the Trieste Heart Muscle Disease Registry. TTNtv were classified according to their site (Z disk, I band, A band, A-M junction, M band) and further grouped for analysis in A-band and non-A band. Variables were expressed as mean±SD, median and interquartile range, or counts and percentage, as appropriate. Kaplan-Meier curves were estimated for the composite endpoints of (i) heart failure-related death, heart transplant, and destination left ventricular assist device implantation and (ii) first major ventricular arrhythmia (MVA, defined as SCD or life-threatening ventricular arrhythmia) and compared by the log-rank test. Results: 154 TTNtv carriers were included in the study, of whom 66% were probands. The most prevalent phenotype was DCM (92%). The mean age of subjects at diagnosis was 43±16 years and 70% were males. There was no difference between groups in the first composite outcome of heart failure-related death, heart transplant, and destination left ventricular assist device implantation. Instead, major ventricular arrhythmias were significantly more frequent in the non-A-band group, in which 47% (n=14) of TTNtv carriers experienced MVA as compared to 19% (n=20) of subjects in the A-band group (p=0.001). Interestingly, we observed a tendency in MVA occurrence at a higher mean left ventricular ejection fraction (LVEF) in the non-A-band group as compared to the A-band group (42±13% vs 35±9%, respectively). Conclusions: Among TTNtv carriers referred to a tertiary center, those with a mutation in the non-A band seem characterized by higher arrhythmic risk. This novel finding highlights the importance of considering the site of TTN truncating variants to guide the most appropriate clinical management for each patient.